PENENTUAN POHON RENTANG MINIMUM PADA DISTRIBUSI JARINGAN LISTRIK BERDASARKAN KONDISI GEOGRAFIS SUATU WILAYAH DENGAN ALGORITMA PRIM STUDI KASUS: JARINGAN LISTRIK DISTRIBUSI PRIMERKOTA SAMARINDA - -, Hadiyanto (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2012)
Determination of the minimum spanning tree are widely used to solve optimization problems of finding solutions to problems that require minmum. In the electricity distribution network, minimum spanning tree (MST) is used to find the minimum length of cable for electricity network system becomes more optimal. Minimum weight of a MST primary distribution power network is strongly influenced by the geographical conditions of a region in the form of contour data. Contour data is spatial data that contains information of the earth surface elevation of an area. To determine the primary distribution grid MST needed an algorithm that can produce optimal solutions. In this research the algorithm used is algorithm Prim. Prim's algorithm is an algorithm in graph theory to find the MST of a weighted graph with emphasis on the selection of minimum weight based on the node is taken. This research was done by designing a model of primary distribution power network graph in accordance with the data obtained. In finding the minimum weight for each side of the network graph should include parameters elevation, high point / node, and the distance between points / nodes. Furthermore, the graph is done by computer calculation and simulation to get the electricity distribution network primary MST using Prim's algorithm with the help of ArcView GIS 3.3 program through the avenue script. Prim's algorithm included in the category of good or efficient algorithms, because the shape of polynomial time complexity in n, where n is a measure of the number of vertices or sides. Based on the test results have shown that the algorithm Prim MST ability to determine the primary distribution grid is much better if based on the geographical conditions of a region. In addition, Prim's algorithm graph computation time in generating the MST based on the data that is not based on the contour and contour data are quadratic. Keywords: minimum spanningtree, prim'salgorithm, contours, complexitytime, distributionÂ electrical network, graph.